Molecular mechanisms of herbicide resistance in rice and kochia - Gupta, Srishti, author; Dayan, Franck E., advisor; Gaines, Todd A., advisor; Reddy, Anireddy, committee member; Kumar, Vipan, committee member (Colorado State University. Libraries, 2024)
Herbicide stress is an important challenge in agriculture and understanding how plants respond to herbicide exposure is crucial for developing effective weed management strategies. Transcription factors (TFs) play a pivotal role in regulating gene expression and mediating plant responses to various environmental stimuli, including herbicide stress. This dissertation aimed to elucidate the role of TFs in herbicide tolerance and sensitivity across plant species. A brief introduction was provided in Chapter 1. Subsequently, by analyzing transcriptomic data from different studies, we identified key TFs involved in herbicide responses. Our findings in Chapter 2 revealed distinct TF signatures, including bZIP, NAC, WRKY, and ERF, that were consistently upregulated in herbicide-tolerant plants. associated with herbicide tolerance or sensitivity, suggesting potential regulatory mechanisms in metabolic pathways and downstream signaling. These results underscore the importance of complex interplay between herbicide class, treatment duration, and plant species on TF expression patterns. In Chapter 3, we focused on herbicide resistance in rice, a critical staple crop. Transcriptomic analysis revealed upregulation of key detoxification genes, including glutathione S-transferase (GST) and cytochrome P450 (CYP450), in the NTSR mutant, suggesting their involvement in herbicide metabolism. Functional characterization confirmed increased glutathione S-transferase activity in the NTSR genotype. Additionally, computational studies identified a novel transcription factor, ZOS-1-16, with a potential role in regulating herbicide response. We investigated a novel non-target site resistance (NTSR) mechanism conferred by a mutation in the transcription factor ZOS-1-16. Our findings demonstrated that ZOS-1-16 upregulates genes like GSTs and CYPs involved in herbicide detoxification, leading to increased resistance to the herbicide quizalofop-p-ethyl (QPE). This study highlights the potential of targeting TFs for developing herbicide-resistant rice varieties. Finally, Chapter 4 explored glyphosate resistance in the invasive species Bassia scoparia (kochia). We investigated the inheritance of glyphosate resistance in kochia populations and found that it is primarily due to an increase in the copy number of the EPSPS (5‐enolpyruvyl‐3‐shikimate phosphate synthase) gene. Additionally, we estimated the outcrossing rate of kochia under field conditions and found a high level of outcrossing, which contributes to the rapid spread of glyphosate-resistant biotypes. Overall, this dissertation provides valuable insights into the role of TFs in herbicide responses and highlights the potential for developing novel strategies to enhance herbicide tolerance and manage herbicide-resistant weeds.
Keywords: kochia; transcription factor; weed science; rice; herbicide resistance; transcriptomics